Interaction of graphene-calcium compound with titanium dioxide clusters: an Ab Initio study - Júnior, José Solon da Silva; Rossato, Jussane; Santos, Cláudia Lange dos (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Titanium dental implants are frequently used, however, in some cases, their utilization results in problems related to inflammations on the tissue. Hence, studies have proposed the use of nanostructures to increase the success rate of the implant. In this work we have studied, through first principles calculations based on the density functional theory, the interaction of the compound graphene-calcium with titanium dioxide clusters (TiO2)n, where n varies from 1 to 3. Graphene was chosen due to its potential applications in several areas of knowledge while the calcium atom is one of the main components of the bones. The obtained results showed a strong interaction between the graphene-calcium system and the (TiO2)n clusters. The calculated values for the adsorption energies vary from 2.41 eV to 4.70 eV. Although the results found have a theoretical character, the graphene-calcium compound is a relevant candidate for the creation of thin films to be used as coating for titanium dental implants.